Cytoarchitectural characteristics associated with cognitive flexibility in raccoons. Issue 14 (20th June 2021) - Jacob, Joanna; Kent, Molly; Benson‐Amram, Sarah; Herculano‐Houzel, Suzana; Raghanti, Mary Ann; Ploppert, Emily; Drake, Jack; Hindi, Bilal; Natale, Nick R.; Daniels, Sarah; Fanelli, Rachel; Miller, Anderson; et al.
Abstract: With rates of psychiatric illnesses such as depression continuing to rise, additional preclinical models are needed to facilitate translational neuroscience research. In the current study, the raccoon ( Procyon lotor ) was investigated due to its similarities with primate brains, including comparable proportional neuronal densities, cortical magnification of the forepaw area, and cortical gyrification. Specifically, we report on the cytoarchitectural characteristics of raccoons profiled as high, intermediate, or low solvers in a multiaccess problem‐solving task. Isotropic fractionation indicated that high‐solvers had significantly more cells in the hippocampus (HC) than the other solving groups; further, a nonsignificant trend suggested that this increase in cell profile density was due to increased nonneuronal (e.g., glial) cells. Group differences were not observed in the cellular density of the somatosensory cortex. Thionin‐based staining confirmed the presence of von Economo neurons (VENs) in the frontoinsular cortex, although no impact of solving ability on VEN cell profile density levels was observed. Elongated fusiform cells were quantified in the HC dentate gyrus where high‐solvers were observed to have higher levels of this cell type than the other solving groups. In sum, the current findings suggest that varying cytoarchitectural phenotypes contribute to cognitive flexibility. Additional research is necessary to determine the translational value of cytoarchitectural distribution patterns on adaptive behavioral outcomes associated with cognitive performance and mental health. Abstract : We confirmed the presence of von Economo neurons in the frontoinsular cortex of all animals. Focusing on problem‐solving ability, raccoons exhibiting high levels of cognitive flexibility had increased total cell counts (via isotropic fractionation) and higher numbers of fusiform cells (via thionin histology) in the hippocampus.